Ortadoğu’da Mavi Su Barışı Yüksek Düzeyli Forum - Kibaroğlu, Ayşegül (MEF Üniversitesi Siyaset Bilimi Uluslararası ilişkiler Bölümü, 2014)
MEF Üniversitesi Siyaset Bilimi Uluslararası ilişkiler Bölümü Öğretim Üyesi Prof. Dr. Ayşegül Kibaroğlu'nun açılış konuşmasını yaptığı uluslararası toplantı MEF Üniversitesi'nde gerçekleşen ilk uluslararası konferans oldu. ‘‘Blue Peace for the Middle East High Level Forum” isimli forum bölge ülkelerinin siyaset, medya ve akademi dünyasından önde gelen kişilerini bir araya getirdi. Irak, Suriye, Lübnan, Ürdün, Yemen, Senegal, Hindistan, İsviçre ve Ülkemizden siyaset, akademi ve medyanın önde gelen temsilcilerini bir araya getiren yüksek düzeyli forum, suyun ortadoğudaki stratejik önemini vurgulamak ve bölge ülkeleri arasında barış ve işbirliğinin geliştirilmesine katkıda bulunmak amacıyla diyalogların geliştirilmesine destek oldu.

About 90 policy makers, Members of Parliament, serving and former Ministers, media leaders, academics and water experts from across the Middle East came together for the first annual High Level Forum on Blue Peace in the Middle East at Istanbul on 19-20 September 2014. The forum was co-hosted by the Strategic Foresight Group and MEF University of Istanbul, Turkey in cooperation with the Swiss Agency for Development and Cooperation and the Political Directorate of the Swiss Federal Department of Foreign Affairs. The participants proposed concrete initiatives at bi-lateral as well as regional levels to promote cooperation and sustainable management of water resources in the region. The Forum began with special presentations on the experience of the Senegal River Basin Authority in collaborative water management and work in progress of Orontes River Basin Atlas for post conflict water management in Syria and its neighbouring countries.
Keywords: Mavi su barışı; Ortadoğu